APPLYING ESA (ENGAGE, STUDY, ACTIVATE) STRATEGY TO IMPROVE STUDENTS’ SPEAKING ABILITY - Ilinawati Ilinawati (VOX EDUKASI: Jurnal Ilmiah Ilmu Pendidikan, 2018)
This study was about improving the teaching of speaking by applying ESA strategy tothestudents of English study program atSTKIP Persada KhatulistiwaSintang in Academic Year 2017/2018. It was a classroom action research (CAR) and  involved the first year students of English language study program. They were poor at speaking. The result of this research showed that ESA strategy succeeded improving the teaching speaking. The mean score was 71,67 in the first cycle and 80,28 in the second cycle. The improvement of the teaching learning process was based on the improvement of teaching learning behavior in the classroom. The change of behavior was notified from the classroom observation, field notes and interview which were discussed with the collaborator in the reflection stage. ESA strategy was found out helpful to improve students speaking ability. Keywords: Speaking, ESA Strategy, Job Interview